Kurikulum Pendidikan Sejarah di Malaysia: Sebagai Bahan Refleksi Pengembangan Kurikulum Sejarah di Indonesia - Nur'aeni Marta (Jurnal Pendidikan Sejarah, 2015)
This article reviewed the history of the educational curriculum in Malaysia. The goal is to describe theeducation system and educational curriculum in Malaysian history. The Malaysian government is awarethat education is a strategic tool in preparing qualified human resources due to the vision or intimation2020 as a common goal to be achieved.. In Malaysian history courses are compulsory subjects taughtat the terrace which learners from grade 4 elementary school to middle school high. Education historyconducted by the Malaysian centric approach. The goal is to instill a sense of nationalism, patriotism andthe formation of the united Malaysian nation.